“Implementación de una máquina prototipo granuladora de caucho de neumáticos fuera de uso” - García Ayala, Stalin Roberto (2020)
The main objective of the project was to build a granulator prototype machine for unused tires rubber (UTR) through the use of recycled materials to minimize costs and to contribute to the environment. The prototype model was carried out by applying the autodesk inventor software in which its operation was designed and simulated. This project generates a high social impact because it is an alternative of generation of employment, so creating a social culture of reusing tires and unused products and giving them a second life. This project issues from the problem of the absence of a tire recycling process in La Maná canton. In addition, tires are thrown away on roads and abandoned pieces of land. This fact causes the reproduction of disease-transmitting mosquitoes and direct burning of tires producing the emission of gases and harmful particles to the atmosphere. In order to achieve the purpose, bibliographic and field research was used. The results of the research conducted on the need of a machine to reuse tires. Thus, the proposal focuses directly on implementing a granulator prototype machine for unused tires rubber which will result in granulated rubber for being used on synthetic floors, courts, and even with another additional process, to be pulverized for first asphalt.